Addition of sialidase or p38 MAPK inhibitors does not ameliorate decrements in platelet in vitro storage properties caused by 4 °C storage. Issue 4 (27th June 2014) - Skripchenko, A.; Thompson‐Montgomery, D.; Awatefe, H.; Turgeon, A.; Wagner, S. J.
<x xml:space="preserve">Abstract</x> Background and Objectives Bacterial proliferation is inhibited in platelets (PLTs) stored at refrigerated temperatures, but also dramatically decreases PLT in vivo survival. Recent studies have demonstrated that cold temperature (CT) stored PLTs secrete sialidases upon re‐warming, removing sialic acid from the PLT surface, which may be responsible for clustering of GPIbα and PLT clearance from circulation. In this study, the influence of a sialidase inhibitor or a p38 MAP kinase inhibitor was evaluated in units stored at 4 °C. Materials and Methods After collection of a single Trima apheresis unit (n = 12), PLTs were aliquoted into four 60‐ml CLX storage bags. One bag was stored at 20–24 °C (RT) with continuous agitation; a second bag was stored at 4 °C without agitation; a third bag was held at 4 °C without agitation with sialidase inhibitor, a fourth bag was incubated at 4 °C with a p38 MAPK inhibitor without agitation. Results Beginning from Day 1, all in vitro PLT parameters were adversely affected by CT compared to those of RT. Similar in vitro storage properties were observed in CT PLT in the presence or absence of sialidase or p38 MAPK inhibitors. P38 MAPK phosphorylation inhibition was not observed at CT. Decrease of sialidase activity was observed for 2 days in PLTs stored in additive solution but not in plasma. Conclusion Addition of either sialidase or p38 MAPK inhibitors do not improve any in vitro parameters of PLTs stored at 4 °C in 100% plasma.